The Barikan Tradition: A Symbol of Solidarity and Communal Harmony - Mohammad Nayaka Rama Yoga; Irvan Ainal Yaqin; Vina Dwi Yulianti; Moh faiq Azimuddin; Novita Mukti Anjarwani; Alicia Taravita Divanadya; Akhriyadi Sofian (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research focuses on the role of the Barikan Tradition in strengthening social solidarity among the community, highlighting how this cultural and religious practice serves as a bond between community members. Additionally, the study aims to explore the religious meanings embedded in the Barikan Tradition from the local community's perspective, as well as its influence on the formation of collective identity. A qualitative approach using ethnographic methods was employed to deeply examine the religious meanings and functions of the Barikan Tradition and its social impact on the community. The findings indicate that the Barikan Tradition is understood as an effort to maintain balance between the spiritual and material worlds, between traditional values and the demands of modernization. This tradition plays a significant role in reinforcing social solidarity, preserving collective identity, and helping the community adapt to social changes. Furthermore, the Barikan Tradition reflects religious syncretism, where a fusion of local beliefs with religion occurs. As a religious rite passed down through generations, Barikan not only functions as a symbolic ritual but also as a reflection of spirituality and community values. In the context of the sociology of religion, this tradition plays an important role in strengthening collective consciousness and preserving religious values amid the challenges of globalization and modernization.